Hydroxychloroquine prevents resistance and potentiates the antitumor effect of SHP2 inhibition in NF1-associated malignant peripheral nerve sheath tumors - Sameer Farouk Sait; Kwan Ho Tang; Steven P. Angus; Rebecca Brown; Daochun Sun; Xuanhua Xie; Charlene Iltis; Michelle Lien; Nicholas D. Socci; Tejus A. Bale; Christopher Davis; Shelley A. H. Dixon; et al. (Proceedings of the National Academy of Sciences, 2025)
Malignant peripheral nerve sheath tumors (MPNSTs) are aggressive sarcomas and the primary cause of mortality in patients with neurofibromatosis type 1 (NF1). These malignancies develop within preexisting benign lesions called plexiform neurofibromas (PNs). PNs are solely driven by biallelic NF1 loss eliciting RAS pathway activation, and they respond favorably to MEK inhibitor therapy. MPNSTs harbor additional mutations and respond poorly to MEK inhibition. Our analysis of genetically engineered and orthotopic patient-derived xenograft MPNST models indicates that MEK inhibition has poor antitumor efficacy. By contrast, upstream inhibition of RAS through the protein-tyrosine phosphatase SHP2 reduced downstream signaling and suppressed NF1 MPNST growth, although resistance eventually emerged. To investigate possible mechanisms of acquired resistance, kinomic analyses of resistant tumors were performed, and data analysis identified enrichment of activated autophagy pathway protein kinases. Combining SHP2 inhibition with hydroxychloroquine (HQ) resulted in durable responses in NF1 MPNSTs in both genetic and orthotopic xenograft mouse models. Our studies could be rapidly translated into a clinical trial to evaluate SHP2 inhibition in conjunction with HQ as a unique treatment approach for NF1 MPNSTs.